Spectroscopic observations and modelling of impulsive Alfvén waves along a polar coronal jet - Jelínek, P.; Srivastava, A. K.; Murawski, K.; Kayshap, P.; Dwivedi, B. N. (EDP Sciences, 2015)
Context. The magnetic reconnection in the solar corona results in impulsively generated Alfvén waves, which drive a polar jet. Aims. Using the Hinode/EIS 2" spectroscopic observations, we study the intensity, velocity, and full width at half maximum (FWHM) variations of the strongest Fe XII 195.12 Å line along the jet to find the signature of Alfvén waves. We numerically simulate the impulsively generated Alfvén waves within the vertical Harris current sheet, forming the jet plasma flows, and mimicking their observational signatures. Methods. Using the FLASH code and an atmospheric model with an embedded, weakly expanding magnetic field configuration within a vertical Harris current sheet, we solve the 2.5-dimensional (2.5D) ideal magnetohydrodynamic (MHD) equations to study the evolution of Alfvén waves and vertical flows forming the plasma jet. Results. At a height of ~5 Mm from the base of the jet, the red-shifted velocity component of Fe' XII 195.12 Å line attains its maximum (5 km s-1), which converts into a blue-shifted velocity component between the altitude of 5-10 Mm. The spectral intensity continuously increases up to 10 Mm, while the FWHM still exhibits low values with an almost constant trend. This indicates that the reconnection point within the jet's magnetic field topology lies in the corona 5-10 Mm from its footpoint anchored in the Sun's surface. Beyond this height, the FWHM shows a growing trend. This may be the signature of Alfvén waves that impulsively evolve, due to reconnection, and propagate along the jet. From our numerical data, we evaluate space- and time- averaged Alfvén waves velocity amplitudes at different heights in the jet's current sheet, which contribute to the non-thermal motions and spectral line broadening. The synthetic width of Fe XII 195.12 Å line exhibits a similar trend of increment as in the observational data, possibly proving the existence of Alfvén waves, impulsively generated by reconnection, that propagate along the jet. Conclusions. The numerical simulations show that the impulsive perturbations in the transversal component of velocity at the reconnection point can excite the Alfvén waves. These waves can power the plasma jet higher into the polar coronal hole, as vertical plasma flows are also associated with these waves due to pondermotive force. The simulated Alfvén waves match well with the observed non-thermal broadening along the jet, which may provide direct spectroscopic evidence of the impulsively excited Alfvén waves within the polar jet.
Keywords: Magnetohydrodynamics (MHD); Methods: numerical; Sun: atmosphere; Sun: corona; Waves